Oxidative stress gene expression profile in inbred mouse after ischemia/reperfusion small bowel injury - Bertoletto,Paulo Roberto (2012)
PURPOSE: To determine the profile of gene expressions associated with oxidative stress and thereby contribute to establish parameters about the role of enzyme clusters related to the ischemia/reperfusion intestinal injury. METHODS: Twelve male inbred mice (C57BL/6) were randomly assigned: Control Group (CG) submitted to anesthesia, laparotomy and observed by 120min; Ischemia/reperfusion Group (IRG) submitted to anesthesia, laparotomy, 60min of small bowel ischemia and 60min of reperfusion. A pool of six samples was submitted to the qPCR-RT protocol (six clusters) for mouse oxidative stress and antioxidant defense pathways. RESULTS: On the 84 genes investigated, 64 (76.2%) had statistic significant expression and 20 (23.8%) showed no statistical difference to the control group. From these 64 significantly expressed genes, 60 (93.7%) were up-regulated and 04 (6.3%) were down-regulated. From the group with no statistical significantly expression, 12 genes were up-regulated and 8 genes were down-regulated. Surprisingly, 37 (44.04%) showed a higher than threefold up-regulation and then arbitrarily the values was considered as a very significant. Thus, 37 genes (44.04%) were expressed very significantly up-regulated. The remained 47 (55.9%) genes were up-regulated less than three folds (35 genes - 41.6%) or down-regulated less than three folds (12 genes - 14.3%). CONCLUSION: The intestinal ischemia and reperfusion promote a global hyper-expression profile of six different clusters genes related to antioxidant defense and oxidative stress.